Tess of the D'Urbervilles - Hardy, Thomas, 1840-1928 (Penguin classics, 2003)
When Tess Durbeyfield is driven by family poverty to claim kinship with the wealthy D'Urbervilles and seek a portion of their family fortune, meeting her 'cousin' Alec proves to be her downfall. A very different man, Angel Clare, seems to offer her love and salvation, but Tess must choose whether to reveal her past or remain silent in the hope of a peaceful future. With its sensitive depiction of the wronged Tess and powerful criticism of social convention, Tess of the D'Urbervilles, subtitled "A Pure Woman," is one of the most moving and poetic of Hardy's novels.